2023
DOI: 10.1038/s41536-023-00293-4
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Brg1 fine-tunes Notch signaling during zebrafish heart regeneration

Abstract: Myocardial Brg1 is essential for heart regeneration in zebrafish, but it remains unknown whether and how endothelial Brg1 plays a role in heart regeneration. Here, we found that both brg1 mRNA and protein were induced in cardiac endothelial cells after ventricular resection and endothelium-specific overexpression of dominant-negative Xenopus Brg1 (dn-xbrg1) inhibited myocardial proliferation and heart regeneration and increased cardiac fibrosis. RNA-seq and ChIP-seq analysis revealed that endothelium-specific … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 72 publications
0
1
0
Order By: Relevance
“…BRG1 localization to promoter regions has been shown to initiate transcription following SWI/SNF-dependent chromatin remodeling [ 81 – 83 ]. There is also evidence to suggest that BRG1 can function as a transcriptional silencer [ 84 ] or regulator of H3K4me3 levels at promoters [ 85 ], highlighting the capacity of the SWI/SNF chromatin remodeling complex to exert versatile transcriptional control. BRG1 can bind both promoters and enhancers, with aberrant BAF complex activity affecting enhancer function and bivalent promoter regulation in cancers [ 86 93 ].…”
Section: Discussionmentioning
confidence: 99%
“…BRG1 localization to promoter regions has been shown to initiate transcription following SWI/SNF-dependent chromatin remodeling [ 81 – 83 ]. There is also evidence to suggest that BRG1 can function as a transcriptional silencer [ 84 ] or regulator of H3K4me3 levels at promoters [ 85 ], highlighting the capacity of the SWI/SNF chromatin remodeling complex to exert versatile transcriptional control. BRG1 can bind both promoters and enhancers, with aberrant BAF complex activity affecting enhancer function and bivalent promoter regulation in cancers [ 86 93 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this process, ECs can also release growth factors and inflammatory cytokines and interact with other cells to promote the regeneration and repair of cardiomyocytes. In one study, the cardiac endothelial Brg1-Kdm7aa-Notch axis was demonstrated to regulate myocardial proliferation and regeneration via modulating the H3K4me3 at notch promoters in zebrafish ( Xiao et al, 2023 ).…”
Section: The Extracellular Microenvironment Of Cardiomyocytes Favors ...mentioning
confidence: 99%